Contexts of risk: mixed methods approach to understanding youth risk and insecurity in post-conflict settings - Taylor, L. K. (Array, 2014)
Identifying contextually-relevant risk factors for youth development is important in settings of intergroup conflict. In Vukovar, Croatia, a city devastated during the fall of the Former Yugoslavia, ethno-political tensions remain and ethnic separation between Croats and Serbs permeates social institutions (Čorkalo et al., 2004). The current study utilized a mixed method approach, including focus groups with adolescents (N=66, age 11 to 15) and a quantitative survey (N=227 ; 58% male), to address two related research questions: (1) What are salient risk factors for developing adolescents in Vukovar? (2) What are the behavioral, cognitive, and emotional responses to these risks? Using the Constant Comparative Method (Maykut & Morehouse, 1994) to analyze focus group discussions, and consistent within emotional security theory (Cummings & Davies, 2010), adolescents distinguished between two types of threat (general/community and inter-ethnic). Moreover, qualitative analyses identified two sets of responses, suggesting distinct community-level insecurity related to each type of risk. Using quantitative scales developed from the focus groups, a path analysis revealed predictive validity between risk and insecurity. First, experience with community antisocial behavior, or general crime found in any context, predicted general insecurity about the community for girls (β=.32, p<.05), but not for boys. Second, community inter-ethnic tension, or those threats related to ethnic identity or the history of war, significantly predicted inter-ethnic insecurity both boys and girls (β=.41, p<.001). That is, controlling or age and Croat/Serb identification, the mixed method approach established the contextual validity and predictive validity of these scales. Implications for future research are discussed.